Treatment of atrial fibrillation with doxapram: TASK-1 potassium channel inhibition as a novel pharmacological strategy. Issue 7 (24th May 2021) - Wiedmann, Felix; Beyersdorf, Christoph; Zhou, Xiao Bo; Kraft, Manuel; Paasche, Amelie; Jávorszky, Natasa; Rinné, Susanne; Sutanto, Henry; Büscher, Antonius; Foerster, Kathrin I; Blank, Antje; El-Battrawy, Ibrahim; et al.
Abstract: Aims: TASK-1 (K2P 3.1) two-pore-domain potassium channels are atrial-specific and significantly up-regulated in atrial fibrillation (AF) patients, contributing to AF-related electrical remodelling. Inhibition of TASK-1 in cardiomyocytes of AF patients was shown to counteract AF-related action potential duration shortening. Doxapram was identified as a potent inhibitor of the TASK-1 channel. In this study, we investigated the antiarrhythmic efficacy of doxapram in a porcine model of AF. Methods and results: Doxapram successfully cardioverted pigs with artificially induced episodes of AF. We established a porcine model of persistent AF in domestic pigs via intermittent atrial burst stimulation using implanted pacemakers. All pigs underwent catheter-based electrophysiological investigations prior to and after 14 days of doxapram treatment. Pigs in the treatment group received intravenous administration of doxapram once per day. In doxapram-treated AF pigs, the AF burden was significantly reduced. After 14 days of treatment with doxapram, TASK-1 currents were still similar to values of sinus rhythm animals. Doxapram significantly suppressed AF episodes and normalized cellular electrophysiology by inhibition of the TASK-1 channel. Patch-clamp experiments on human atrial cardiomyocytes, isolated from patients with and without AF could reproduce the TASK-1 inhibitory effect of doxapram. Conclusion: Repurposing doxapram might yield a promising new antiarrhythmic drug to treat AF in patients. Graphical Abstract: Abstract : Translational perspective Pharmacological suppression of atrial TASK-1 potassium currents prolongs atrial refractoriness with no effects on ventricular repolarization, resulting in atrial-specific class-III antiarrhythmic effects. In our preclinical pilot study, the respiratory stimulant doxapram was successfully administered for cardioversion of acute AF as well as rhythm control of persistent AF in a clinically relevant porcine animal model.